Analysis of Illocutionary Speech Acts in Bawaslu RI Podcast Episode 32: : “Pengawasan Partisipatif” With Lolly Suhenty - Hamrana Hakim Ana; Aslan Abidin; Muh. Hasbi (Faculty of Education and Teacher Training of UIN Palopo, 2026)
This study aims to examine the forms and functions of illocutionary speech acts in Bawaslu RI Podcast Episode 32: “Pengawasan Partisipatif”, featuring Lolly Suhenty as the guest speaker. The phenomenon under investigation arises from the increasing use of digital media as a means of public communication for state institutions, which requires effective language strategies to deliver persuasive messages to the public. The research employs a qualitative case study approach, as it focuses on a single communication event analyzed in depth. Data were collected through documentation techniques in the form of a full transcript of the podcast episode, supported by content analysis and a review of relevant literature. The unit of analysis consists of all utterances by the speaker that contain potential illocutionary speech acts. The analysis reveals three dominant categories of illocutionary acts: directive, representative, and commissive. Directive acts reflect invitations and encouragement for the public to participate actively in election oversight. Representative acts appear in the form of explanations, factual statements, and clarifications regarding the mechanisms of participatory monitoring. Meanwhile, commissive acts demonstrate Bawaslu’s commitment to expanding education and collaborative oversight. These three types of illocutionary acts play a crucial role in constructing persuasive communication and strengthening the relationship between Bawaslu and the public. This study contributes to the development of pragmatic research within the context of digital institutional communication and offers practical implications for Bawaslu in designing more effective public communication strategies. Future research is recommended to broaden the data sources across various podcast episodes or other digital communication platforms to obtain a more comprehensive understanding.